Al-HADITH AL-MIHNIYYA: Mafhum Rais al-Daula al-Nabawi - Magfirah, Siti; Subhan, Zaitunah (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2022)
Hadith of Professionalism: the Concept of the Head of State of the Prophet. The focus of this study is to analyze the characteristics of the head of state of the Prophet Muhammad when in Madinah based on a review of professionalism hadiths. The purpose of this research is to explain the role of the Prophet Muhammad in Madinah when he served as head of state and to find out the quality of hadith in the form of analysis of professional hadiths. This research approach uses hadith, philosophical and political criticism. The type of research used is qualitative, including primary data sources, namely data obtained directly from hadith source books and secondary data, namely obtained from the results of writings that have been systematized in the form of books and journals. The methodology used by this study is takhrij al-hadith and hadith criticism which is used as a tool for measuring the studyofhadith. The result of this research is that the hadiths of professionalism in this study are included in the category of sahih hadith and can be used as an argument as a study of the criticism of sahih hadith in the book of al-Bukhari, Muslim and Ahmad Ibn Hanbal. The conclusions of this study show that leadership hadiths on professionalism have accommodated the role of the Prophet Muhammad as head of state, because it is covered in prophetic leadership characteristics such as: the ability to carry out trust, equalize justice for society, realize the advantages and weaknesses of the self, be honest and the ability to fight against the enemy. The implementation of this paper is the position of the Prophet Muhammad (peace be upon him) cannot be separated from the guidance of Allah swt regarding the ability to lead so that success in the head of state when in Medina is conveyed through the professionalism possessed by the Prophet.[Fokus penelitian ini adalah menganalisa karakteristik kepala negara Nabi Muhammad saw ketika di Madinah berdasarkan tinjauan hadis-hadis profesionalisme. Tujuan penelitian ini adalah menjelaskan peran Nabi Muhammad saw di Madinah ketika menjabat sebagai kepala negara serta untuk mengetahui kualitas hadis dalam wujud analisis hadis-hadis profesionalisme. Pendekatan penelitian ini menggunakan kritik hadis, filosofis dan politik. Jenis penelitian yang digunakan adalah kualitatif di antaranya sumber data primer yaitu data yang diperoleh langsung dari kitab sumber hadis dan data sekunder yaitu diperoleh dari hasil tulisan yang telah disistematisasi berupa buku-buku dan jurnal. Adapun metodologi yang digunakan penelitian ini ialah takhrij al-hadis dan kritik hadis yang dijadikan sebagai alat bantu untuk tolak ukur penelitian hadis. Hasil penelitian ini ialah hadis-hadis profesionalisme dalam penelitian ini masuk dalam kategori hadis sahih dan dapat dijadikan hujah sebagaimana telaah kritik hadis sahih dalam kitab al-Bukhari, Muslim dan Ahmad Ibn Hanbal. Kesimpulan pada penelitian ini menunjukkan bahwa hadis-hadis kepemimpinan tentang profesionalisme telah mengakomodasi peran Nabi Muhammad saw sebagai kepala negara, sebab tercakup dalam karakteristik kepemimpinan profetik seperti: kemampuan dalam mengemban amanah, mengimbangi keadilan untuk masyarakat, menyadari kelebihan dan kelemahan diri, berlaku jujur serta kemampuan berperang melawan musuh. Adapun implementasi tulisan ini ialah posisi Nabi Muhammad saw tidak terlepas dari tuntunan dari Allah swt terkait kemampuan dalam memimpin sehingga kesuksesan dalam kepala negara ketika di Madinah tersampaikan melalui sikap profesionalisme yang dimiliki oleh Nabi.]